General Elections and Technology: Realising Transparency and Integrity in Elections - Taufiq Yuli Purnama; Retno Catur Kusuma Dewi; Anik Tri Haryani (Faculty of Law, Universitas Slamet Riyadi, 2024)
This project aims to enhance the utilisation of technology, particularly digital technology, in the execution of elections in a democratic nation such as Indonesia. The 2024 General Election is expected to encounter numerous problems, necessitating the digitalization of democracy to streamline the implementation of future General Elections. The usage of digital technology, particularly social media, is essential for the execution of future General Elections to streamline the electoral process and serve as a conduit for communication and information to the public or voters. This study employs normative legal research methodologies, analysing library materials that include primary legal sources such as Law Number 7 of 2017 regarding General Elections, Law Number 1 of 2024 about the Second Amendment of Law Number 11 of 2008 on Electronic Information and Transactions, and General Election Commission Regulation Number 15 of 2023 concerning General Election Campaigns, as well as secondary legal sources comprising books, journals, and other literature. The research indicates that the implementation of digital technology is anticipated to enhance voter participation and the quality of democracy in Indonesia, mitigate fraud, foster more transparent, accountable, and sustainable elections, and alleviate issues that arise during General Elections. Conversely, enhancing the competencies of election organisers is essential to elevate professionalism and mitigate errors